Event segmentation: cross-linguistic differences in verbal and non-verbal tasks - Gerwien, Johannes; Stutterheim, Christiane von (Cognition, 2018)
Events, as fundamental units in human perception and cognition, are limited by quality changes of objects over time. In the present study, we investigate the role of language in shaping event units. Given fundamental cross-linguistic differences in the concepts encoded in the verb, as in French compared to German, event unit formation was tested for motion events in a verbal (online event description, experiment 1), as well as a non-verbal task (Newtson-test, experiment 2). In German, motion and direction are described by a single assertion, i.e. one verb encoding manner (to walk …), in conjunction with adpositional phrases for path and direction (… over x across y toward z). In contrast, when information on path and direction is encoded in the verb, as typically in French, each path segment requires a separate assertion (head for x, cross y, approach z). Both experiments were based on short naturalistic video clips showing a figure moving through space along a path either without changing orientation/direction (control), or with changes in orientation/direction (critical). Analysis of the verbal task concerned the probability of producing more than one assertion to refer to the motion events presented in the clips; in the non-verbal event segmentation task, the analysis concerned the probability of marking an event boundary, as indicated by pressing a button. Results show that in French, the probability of producing more than one assertion was significantly higher in the critical condition (experiment 1) and the probability to identify an event boundary was also significantly higher (experiment 2), compared to the German participants but only in the critical condition. The findings indicate language-driven effects in event unit formation. The results are discussed in the context of theories of event cognition, thereby focusing on the role of language in the formation of cognitive structures.
Gesehen am 01.04.2019